Re-engineering of Products and Processes How to Achieve Global Success in the Changing Marketplace - Rotini, Federico; Borgianni, Yuri; Cascini, Gaetano (Springer Series in Advanced Manufacturing, 2012)
Whilst previous methods for business process re-engineering have focused on time and cost reduction policies to preserve competitive services and products, Re-engineering of Products and Processes: How to Achieve Global Success in the Changing Marketplace presents a new approach which aims to include aspects that impact the customer perceived value. This method supports business re-engineering initiatives by identifying process bottlenecks as well as new products and services available to overcome market competition. This original approach is described step-by-step, explaining the theory through examples of performable tasks and the selection of relevant tools according to the nature of the problem. Supported by illustrations, tables and diagrams, Re-engineering of Products and Processes: How to Achieve Global Success in the Changing Marketplace clearly explains a method which is then applied to several case studies across different industrial sectors. Re-engineering of Products and Processes: How to Achieve Global Success in the Changing Marketplace provides a scientific reference for researchers and PhD students working in several fields of Industrial Engineering: mechanical, electric, electronic sectors and, more generally, all areas of industry where there are needs to design innovative products. The step-by-step description on how to employ the proposed method and its application to practical examples make the book a key resource for industry consultants and manager looking to increase the value of their products and services for new and existing customers. y>.